Bilateral propellers dynamic control for an underwater operated vehicle using a self-synchronization practical tracking controller. (15th February 2018) - Pu, Yu-Chi; Kuo, Chao-Lin; Chen, Jian-Liung; Lin, Chia-Hung; Yan, Jun-Juh
Abstract: This paper proposes the station-keeping control for an underwater vehicle keeping balance motions and performing accurate manipulations in underwater inspections. In order to control position and maintain bilateral balance in deep water, a controller is designed with a Sprott system-based self-synchronization error formulation and a bisection approach algorithm to enhance the performances of brushless dc motors. A sufficiently high but not exceeding metacentric height (GM) is designed for the proposed underwater vehicle. Depth control with a pressure sensor is carried out depth gauge to determine the operated voltages. Using the voltage control mode, the practical tracking controller can maintain the same dynamics for bilateral propellers. Uncertainty dynamic parameters cannot be precisely modeled in a vehicle, and another one can track the pre-specified dynamic responses of a reference model. It keeps the bilateral propeller balancing operations by close-loop controlling the duty ratios of a buck-boost converter. In contrast with the incremental conductance based controller and PID controller, the proposed bilateral propellers controller is used to demonstrate the superior performances in depth and station-keeping tests, operating with armature voltages of 0–30 VDC and rotor speeds of 0–900 rpm in 0–3 m diving depth. Highlights: Keep bi-propeller balance. Operate via voltage controller. Design in an embedded system.